Virtual Assistant Platform - Kužnar, Damjan; Tavčar, Aleš; Zupančič, Jernej; Duguleana, Mihai (Informatica, 2016)
In this paper a novel virtual assistant platform is presented. The platform allows for easy creation, administration, and use of virtual assistants as additional services on websites and as a stand-alone application on mobile platforms. The implementation is based on the principle of Software as a Service, which significantly eases the installation and maintenance of the system and consequently reduces costs